The palladium-catalyzed asymmetric synthesis of 4'-disubstituted nucleoside analogs and studies towards the total synthesis of plakevulin A - Hervert, Katherine L., author; Hegedus, Louis S., advisor; Dorhout, Peter K., committee member; Fisher, Ellen R., committee member; Inamine, Julia M., committee member; Kennan, Alan J., committee member (Colorado State University. Libraries, 2004)
4'-substituted nucleoside analogues have been synthesized using palladium-catalyzed asymmetric allylic amination conditions. A kinetic discrimination between the diastereomeric lactol acetates afforded the desired aminated products and recovered α-acetate in high yields and <97:3 diastereoselectivity. Epimerization of the recovered lactol acetate produced a 60:40 α:β mixture which could be resubjected, in principle, to the palladium-catalyzed asymmetric allylic amination conditions. Studies were conducted towards an enone intermediate for synthesis of plakevulin A. Progress was hindered by the discovery that the wrong regioisomer was obtained from a Lewis acid catalyzed sulfur ylide ring expansion reaction. NMR spectroscopy was utilized for a comparative analysis between model systems for structure elucidation of the product from the BF3·OEt2 catalyzed ethyl diazoacetate ring expansion reaction.
Keywords: organic chemistry